PENGARUH APLIKASI KOMPOS TEA FLUFF DAN Azotobacter sp. TERHADAP SIFAT FISIK TANAH DAN PERTUMBUHAN BIBIT PADA PERSEMAIAN TEH - Cahyani Dewi; Restu Wulansari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
The tea plantation industry in West Java is experiencing problems with the degradation of organic matter, which can be seen from the decrease in organic C in the Bandung area and the large amount of factory solid waste produced every day. The provision of solid tea fluff as organic matter by composting can be a solution to improve the physical properties of the soil in tea plantations, and it is necessary to provide indigenous microbes to maximize plant growth in the form of Azotobacter sp. This study used a factorial randomized block design with two factors, namely soil media 100% topsoil + 0% tea fluff (F0), 70% topsoil + 30% tea fluff (F1), 60% topsoil + 40% tea fluff (F2). ), 50% topsoil + 50% tea fluff (F3), 40% topsoil + 60% tea fluff (F4), 30% topsoil + 70% tea fluff (F5) with an additional dose of Azotobacter sp. 0 mL (A0) and 3 mL (A1). The results for the soil unit weight parameter were significantly different (p<0.05), and there was an interaction between the soil media treatments and Azotobacter sp. all treatments experienced a decrease in bulk density, while the porosity parameter was not significantly different. However, for plant parameters, the F0A0 treatment showed better results than other treatments on the initial growth of tea seedlings.